Efektifitas Terapi Nebulisasi untuk Mengatasi Bersihan Jalan Napas Tidak Efektif pada Anak dengan Bronkopneumonia - Atika Rahmawati; Syahruramadhani Syahruramadhani (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Airway clearance is a condition in which the production of secretions is excessive so that secretions accumulate in the bronchi which interferes with the airway which can result in obstruction of the airway and can interfere with meeting oxygen needs. The purpose of this study is to determine the effectiveness of giving nebulization therapy to overcome ineffective airway clearance in children with bronchopneumonia. The method in this case study is to use a comprehensive nursing care approach which includes assessment, enforcement of nursing diagnoses, planning (outcomes & interventions) of nursing, implementation of nursing and evaluation of nursing which is used for 3 days for 20-30 minutes by providing nebulization therapy. The results of the study showed that there was an effect of nebulization therapy on patients after nebulization therapy for 3 days which showed that the patient's coughs and colds were reduced. Secretions have been able to come out and secret production has been reduced. Then the patient also looks calmer and doesn't cough as often. Providing interventions related to airway management with nebulization therapy in patients with ineffective airway clearance nursing problems indicates that nebulization therapy is effective in helping reduce patient coughing, removing secretions and reducing secretion production.